What Is Constructionism in Psychiatry? From Social Causes to Psychiatric Classification - van Riel, Raphael (Frontiers in Psychiatry, 2016)
It is common to note that social environment and cultural formation shape mental disorders. The details of this claim are, however, not well understood. The paper takes a look at the claim that culture has an impact on psychiatry from the perspective of metaphysics and the philosophy of science. Its aim is to offer, in a general fashion, partial explications of some significant versions of the thesis that culture and social environment shape mental disorders, and to highlight some of the consequences social constructionism about psychiatry has for psychiatric explanation. In particular, it will be argued that the alleged dependence of facts about particular mental disorders and about the second order property of being a mental disorder on social facts amounts to a robust form of constructivism, whereas the view that clinician-patient interaction is influenced by cultural facts is perfectly compatible with an anti-constructivist stance.